Bandwidth Enhancement of Proximity-Coupled Patch Antenna Using Dual Open-Ended Ring-Shaped Slots for Sub-6 GHz Applications - Rheyuniarto Sahlendar Asthan; Mia Maria Ulfah (Jurnal Teknik Elektro, 2026)
This paper presents a bandwidth enhancement of patch antenna intended for sub-6 GHz applications. A square-shaped radiating patch is configured on a double-layer FR-4 dielectric substrates with a dielectric constant of 4.3 and a total thickness of 3.2 mm. To improve the impedance bandwidth, the antenna is fed using proximity-coupling method, in which the microstrip feeding line and the ground plane are placed on the top and bottom layers of the second substrate. Dual open-ended ring-shaped slots are subsequently introduced and etched on the radiating patch element to further enhance the antenna bandwidth. Various slot structures are evaluated, and their physical parameters are varied in a parametric study to analyze their effect on antenna performance, particularly impedance bandwidth. The proposed antenna has a compact dimension of 0.38λ0×0.38λ0×0.06λ0 and exhibits wideband characteristics with a fractional bandwidth of 22.3%.